Chiral Hybrid Perovskite Single‐Crystal Nanowire Arrays for High‐Performance Circularly Polarized Light Detection. Issue 21 (24th September 2021) - Liu, Zhen; Zhang, Chunhuan; Liu, Xiaolong; Ren, Ang; Zhou, Zhonghao; Qiao, Chan; Guan, Yuwei; Fan, Yuqing; Hu, Fengqin; Zhao, Yong Sheng
Abstract: Circularly polarized light (CPL) detection has emerged as a key technology for various optoelectronics. Chiral hybrid perovskites (CHPs) that combine CPL‐sensitive absorption induced by chiral organic ligands and superior photoelectric properties of perovskites are promising candidates for direct CPL detection. To date, most of the CHP detectors are made up of polycrystalline thin‐film, which results in a rather limited discrimination of CPL due to the existence of redundant impurities and intrinsic defect states originating from rapid crystallization process. Here, it is developed a direct CPL detector with high photocurrent and polarization selectivity based on low‐defect CHP single‐crystal nanowire arrays. Large‐scale CHP nanowires are obtained through a micropillar template‐assisted capillary‐bridge rise approach. Thanks to the high crystallinity and ordered crystallographic alignment of these arrays, a CPL photodetector with high light on/off ratio of 1.8 × 10 4, excellent responsivity of 1.4 A W −1, and an outstanding anisotropy factor of 0.24 for photocurrent has been achieved. These results would provide useful enlightenment for direct CPL detection in high‐performance chiral optoelectronics. Abstract : An efficient circularly polarized light (CPL) detector is demonstrated with large‐scale chiral hybrid perovskite (CHP) nanowire arrays. Based on the high photocurrent and polarization selectivity of CHP single‐crystals, high‐performance CPL detectors with high light on/off ratio and excellent polarization distinguishability through arranging such single‐crystalline CHP nanowires into low‐defect arrays are achieved.